Greening China's Urban Governance Tackling Environmental and Sustainability Challenges - Delman, Jørgen; Ren, Yuan.; Luova, Outi.; Burell, Mattias; Almén, Oscar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume examines how urban stakeholders in China - particularly city governments and social actors - tackle China's urban environmental crisis. The volume's case studies speak to important interdisciplinary themes such as new tools and instruments of urban green governance, climate change and urban carbon consumption, green justice, digital governance, public participation, social media, social movements, and popular protest. It lays out a unique theoretical framework for examining and discussing urban green governance. The case studies are based on extensive fieldwork that examines governance failures, challenges, and innovations from across China, including the largest cities. They show that numerous policies, experiments, and reforms have been put in place in China - mostly on a pragmatic basis, but also as a result of both strategic policy design, civil participation, and protest. The book highlights how China's urban governments bring together diverse programmatic building blocks and instruments, from China and elsewhere. Written by experts and researchers from different disciplines at leading universities in China and the Nordic countries in Europe, this volume will be of interest to researchers and students who are interested in Chinese politics, especially urban politics, governance issues, and social movements. Both students and teachers will find the theoretical perspectives and case studies useful in their coursework.The unique green governance perspective makes this a work that is empirically and theoretically interesting for those working with urban political and environmental studies and urbanization worldwide.
Preface -- Introduction: Getting to grips with China's emerging green urban governance -- LIST OF CONTENTS -- LIST OF ABREVIATIONS -- I Green urban governance - a theoretical perspective -- Chapter 1 Wider theoretical debates on urban sustainability governance -- II Policy mobilization, planning, and implementation -- Chapter 2 Are model cities an effective instrument for urban environmental governance? -- Chapter 3 Environmental Planning and "Multi-planning Integration" in China -- Chapter 4 Environmental policies enter the educational sector: Different shades of green at district level -- Chapter 5 Urban water management in Beijing and Copenhagen: Sustainability, climate resilience, and the local water balance -- Chapter 6 Direct carbon emissions by urban residents and characteristics of high emitters: The case of Shanghai -- III The state's new tools of green urban governance -- Chapter 7 Digital environmental monitoring in urban China -- Chapter 8 Performance reviews, public accountability and green governance in Hangzhou -- IV Society knocking on the door -- Chapter 9 Digital media, cycles of contention, and urban governance in China - Anti-PX protests as an example of the sustainability of environmental activism -- Chapter 10 The role of social protests in environmental governance in Hangzhou -- Chapter 11Green justice approach to the environmental governance dilemma: A case study of Jiufeng Environmental Energy Project in Yuhang District, Hangzhou -- Chapter 12 Civic engagement and sustainable development in urban China: Policy lobbying by social organizations -- Epilogue: New perspectives on China's emerging green urban governance -- Contributors -- Index.
Keywords: Sociology, Urban; Political science; Sustainability; Urban Sociology; Political Science; Sustainability